Drought-tolerant teff grass as an alternative forage for dairy cattle - Saylor, Benjamin Anthony (Kansas State University, 2017)
Declining ground water supplies are putting significant pressure on the dairy industry in the United States. The water needed for forage production represents the great majority of total water use on most dairy farms, posing a major challenge in the pursuit of improved drought resilience. Teff (Eragrostis tef), a drought-tolerant annual grass (C4 physiology) native to Ethiopia, could prove an attractive alternative to traditional forage crops. While teff grass has potential to fit the needs for forage production in water-stressed regions, very little is currently known about its nutritional characteristics and whether it can support high levels of milk production by dairy cattle. An experiment was conducted to investigate the effects of variety and cutting age on dry matter yield, nutritive values, and digestibility of teff grass. Eighty pots were blocked by location in a greenhouse and randomly assigned to 4 teff varieties (Tiffany, Moxie, Corvallis, and Dessie) and to 5 cutting ages (40, 45, 50, 55, or 60 d after planting [DAP]). Results from this study indicate that, under greenhouse conditions, the first cutting of teff grass should be harvested at 45 to 50 DAP to optimize forage yield, quality, and digestibility in that cutting and in subsequent cuttings. A second experiment was conducted to assess the productivity of lactating dairy cows fed diets with teff hay as the sole forage. Nine multiparous Holstein cows were randomly assigned treatment sequence in a 3 × 3 Latin square design. Diets were either a control, where dietary forage consisted of a combination of corn silage, alfalfa hay, and prairie hay, or 1 of 2 teff diets, where teff hay was the sole forage. The teff diets maintained yields of milk and milk fat while increasing milk protein yield. Together, these two studies suggest that teff-based diets have potential to maintain high levels of milk production while improving the resilience of the dairy industry to future water shortages.
Keywords: Drought; Teff grass; Dairy cattle